IMPLEMENTASI KEBIJAKAN PAJAK PENGAMBILAN DAN PENGOLAHAN BAHAN GALIAN GOLONGAN C DI KABUPATEN MERAUKE - Edoardus E Maturbongs (Societas : Jurnal Ilmu Administrasi dan Sosial, 2012)
The aims of the research are to (1) explain the process of policy implementation of acquisition and processing tax of class C mineral, (2) explain the factors affecting policy implementation of acquisition and processing tax of class C mineral in Merauke Regency. The research was conducted in Merauke Regency by using qualitative method. The data were obtained through observation, interview, and documentation. The informants were taken from Regional Revenue Department and Mining and Energy Department of Merauke and community.The results of the research reveal that implementation process involves tax payment of any mining activity. License for mining activities and sanctions for those who break any rules do not run well. Meanwhile, the affecting factors consisting of realtionship among organizations, behaviour of lower officials, and target group still need improving especially to increase human resources as the policy implementers.